Japanese Culinary Industry in South Asia: An Exploratory Comparison of Indian and Bangladeshi Consumers - MD. SAIFULLAH AKON; DEBASISH NANDY (The Journal of Indian and Asian Studies)
With the South Asian economy swiftly integrating into global markets, the restaurant industry in India and Bangladesh has thrived, providing a wide range of global cuisines. Along with other foreign restaurants, Japanese restaurants have gained traction in recent years. This paper seeks to delve into the Japanese culinary industry in South Asia, aiming to comprehend the factors influencing consumer choice and formulate an effective market development strategy. Employing the theory of planned behavior (TPB), the study explores the determinants of Indian and Bangladeshi consumers’ intentions to choose Japanese restaurants. Utilizing qualitative research methods, 36 in-depth interviews (IDIs) were conducted, with 20 Indian and 16 Bangladeshi respondents. A semi-structured questionnaire covering demographics, attitudes, subjective norms (SN), perceived behavioral control and other factors including price concern, food authenticity and religion was employed. Analysis of interview transcripts using NVivo 10 software revealed that participants generally had an average economic condition. Notably, religion emerged as a significant factor influencing purchase intentions in Bangladesh, while attitude and perceived behavioral control are the most significant contributors to Indian consumers’ perceptions. Additionally, the study found that both Indian and Bangladeshi consumers’ perceptions were significantly influenced by the authenticity of Japanese cuisine and food prices positively and negatively. The findings offer valuable insights into the Japanese culinary industry promotion in India and Bangladesh.